2000
DOI: 10.1007/s004240000081
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene polymorphism as a cardiovascular risk factor in children

Abstract: A family history of cardiovascular disease predicts cardiovascular risk in the next generation, which is either the result of inherited traits or certain living habits in some families. The aim of our study was to evaluate both variables and particularly the role of one of the possible genetic risk factors--angiotensin-converting enzyme (ACE) gene polymorphism. History and anthropometric and biochemical parameters, ACE gene polymorphism and carotid wall thickness--intima media thickness (IMT) were studied in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…14 -39 Two studies that used family-based design were excluded. 24,31 One study did not report detailed statistics for IMT measurement 37 and therefore was not included in the meta-analysis. Furthermore, 2 case-control studies did not report detailed results of their controls groups, 19,39 and only case groups were included.…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 -39 Two studies that used family-based design were excluded. 24,31 One study did not report detailed statistics for IMT measurement 37 and therefore was not included in the meta-analysis. Furthermore, 2 case-control studies did not report detailed results of their controls groups, 19,39 and only case groups were included.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Some studies found a positive association between the D allele and IMT, 14 -20 whereas others failed to find such a relation. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] However, the studies were conducted in selective and heterogeneous groups from low-risk populations to hypertensive or diabetic patients. Furthermore, the sample sizes of these studies have been relatively small.…”
mentioning
confidence: 99%